Proceedings of the 4th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle 2007
DOI: 10.17077/drivingassessment.1236
|View full text |Cite
|
Sign up to set email alerts
|

Near Peripheral Motion Detection Threshold Predicts Detection Failure Accident Risk in Younger and Older Drivers

Abstract: Summary: Motion contrast thresholds for 0.4 cycle/degree drifting Gabor stimuli were assessed at 15-degrees eccentricity for 16 younger drivers (ages 24 to 42), and 15 older drivers (ages 65 to 84), using a temporal two-alternative forced choice staircase procedure. Two self-report questionnaires assessed detection failure accident risk-the Driver Perception Questionnaire (DPQ5), and an abridged Aging Driver Questionnaire (ADQ15). The UFOV ® test battery was also administered. Mean peripheral motion contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Reaction time scores using the low-cost desktop simulator with respect to crash occurrence and age group. ability for older adults whereas driving ability among younger age groups may be better explained by driving styles (Anstey et al, 2005;Ball et al, 2006;Classen et al, 2008;Clay et al, 2005;Henderson et al, 2007Henderson et al, , 2009Lee et al, 2002;Rizzo et al, 2004).…”
Section: Serializationmentioning
confidence: 99%
“…Reaction time scores using the low-cost desktop simulator with respect to crash occurrence and age group. ability for older adults whereas driving ability among younger age groups may be better explained by driving styles (Anstey et al, 2005;Ball et al, 2006;Classen et al, 2008;Clay et al, 2005;Henderson et al, 2007Henderson et al, , 2009Lee et al, 2002;Rizzo et al, 2004).…”
Section: Serializationmentioning
confidence: 99%
“…PMCT was very strongly associated with UFOV2, suggesting that the two vision measures tap common or overlapping visual functions, as Henderson et al (2007) had suggested. PMCT was very strongly associated with crashes and with drivers' overall assessed simulator performance (G2-rater), and strongly with Missed Stops.…”
Section: Resultsmentioning
confidence: 55%
“…For example, at-risk drivers could restrict the length of their glances away from the driving environment to well under two seconds (Henderson et al, 2007). In addition, research could determine if training in voluntary scanning techniques (Scheiber, 1998) offers an effective countermeasure for the deficit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations